Structural optimization using the boundary element method and topological derivative applied to a suspension trailing arm. Issue 10 (3rd October 2018) - Anflor, C. T. M.; Teotônio, K. L.; Goulart, J. N. V.
ABSTRACT: This work investigates the optimization of elasticity problems using the boundary element method (BEM) as a numerical solver. A topological shape sensitivity approach is used to select the points showing the lowest sensitivities. As the iterative process evolves, the original domain has portions of material progressively removed in the less efficient areas until a given stop criterion is achieved. Two benchmark tests are investigated to demonstrate the influence of the boundary conditions on the final topology. Following this, a suspension trailing arm is optimized and a new design is proposed as an alternative to commercially available methods. A postprocedure of smoothing using Bézier curves was employed for the final topology of the trailing arm. This process allowed the external irregular shapes to be overcome. The BEM coupled with the topological derivative was shown to be an alternative to traditional optimization techniques using the finite element method. The present methodology was shown to be efficient for delivering optimal topologies with few iterations. All routines used were written in open code.